2016
DOI: 10.17795/ijcp.3900
|View full text |Cite
|
Sign up to set email alerts
|

Barriers for Early Detection of Cancer Amongst Urban Indian Women: A Cross Sectional Study

Abstract: Background:Cancer is a leading cause of death globally. Every year, millions of cancer patients could be saved from premature death and and suffering if they had timely access to early detection and treatment. There are two main components of early detection: early diagnosis and screening. In India, cancers of cervix, breast, mouth/oropharynx are the most frequent cancers in women. These cancers are amenable to early detection. More than two third of the cancer patients are already in an advanced and incurable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Studies done in India and among South Asian women also obtained lack of knowledge of method of performance and fear of finding a lump as reasons for not performing BSE. 19,20 One hundred and sixty three women (88.5%) did it in the bathroom, while 12 (6.5%) did it in front of a mirror and 9 (5%) did it while lying down on bed.…”
Section: Practicementioning
confidence: 99%
“…Studies done in India and among South Asian women also obtained lack of knowledge of method of performance and fear of finding a lump as reasons for not performing BSE. 19,20 One hundred and sixty three women (88.5%) did it in the bathroom, while 12 (6.5%) did it in front of a mirror and 9 (5%) did it while lying down on bed.…”
Section: Practicementioning
confidence: 99%
“…In another study done on the female personnel of Walailak University, the knowledge of BCS was very high (Kotepui et al, 2015). The main barrier for cancer screening is the low level of cancer awareness (Kadam et al, 2016). Usually positive changes in the attitude of people occur as a result of increasing awareness and their education.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that living in rural areas can affect the access to breast cancer diagnostic tools, potentially resulting in delays in cancer diagnosis [387]. Additionally, being far from primary health centers and hospitals, prevents the availability of treatment, surgery, or appropriate interventions, decreasing the possibility of positive outcomes and patient recovery [387][388][389][390]. Another issue is the discomfort and stress that is generated during screening and diagnostic procedures that reduce the willingness of patients to perform the tests [11][12][13][14].…”
Section: Issues With Current Screening and Diagnostic Tools: The Need For New Or Improved Techniquesmentioning
confidence: 99%